Age-dependent association between lifestyle oxidative balance score and bone mineral density in children and adolescents: evidence from the NHANES 2015–2018 - Li, Suman; Mao, Yuan (Frontiers in Physiology, 2025)
BackgroundOxidative balance score (OBS) integrates pro- and antioxidant exposures, potentially influencing skeletal health. This study aimed to examine the association between OBS with bone mineral density (BMD) in children and adolescents.MethodsIndividuals aged ≤18 years from the National Health and Nutrition Examination Survey were included. The OBS was determined based on four lifestyle factors and sixteen dietary nutrients. Baseline characteristics were compared by gender. Generalized linear regression models were utilized to assess the relationships between total, lifestyle, and dietary OBS with lumbar spine, pelvis, and total BMD. Interaction and subgroup analyses were used to examine age-related modifications. The mediation effect of oxidative stress-related indicators in the relationship between OBS and BMD was analyzed using mediation analysis.ResultsFinally, 1196 children and adolescents with a median age of 13 years were included. Lifestyle OBS showed a significant positive correlation with all BMD measures. However, the association reversed to a negative correlation after adjusting for confounders. Sensitivity analysis identified age as a key modifier. Subgroup analysis revealed that lifestyle OBS positively correlated with lumbar spine and total BMD in younger individuals (≤13 years) but negatively correlated with all BMD measures in older participants (>13 years). A nonlinear relationship between lifestyle OBS and BMD was observed. Higher lifestyle OBS was associated with greater physical activity and lower cotinine levels. Additionally, uric acid and GGT were the potential mediators between lifestyle OBS and BMD.ConclusionLifestyle OBS exhibits an age-dependent association with BMD. These findings highlight the importance of age considerations in lifestyle-BMD research and potential implications for bone health strategies in youth.